Calcium supplementation decreases BCP-induced inflammatory processes in blood cells through the NLRP3 inflammasome down-regulation. (15th July 2017) - Lagadec, Patricia; Balaguer, Thierry; Boukhechba, Florian; Michel, Grégory; Bouvet-Gerbettaz, Sébastien; Bouler, Jean-Michel; Scimeca, Jean-Claude; Rochet, Nathalie
Graphical abstract: Abstract: Interaction of host blood with biomaterials is the first event occurring after implantation in a bone defect. This study aimed at investigating the cellular and molecular consequences arising at the interface between whole blood and biphasic calcium phosphate (BCP) particles. We observed that, due to calcium capture, BCP inhibited blood coagulation, and that this inhibition was reversed by calcium supplementation. Therefore, we studied the impact of calcium supplementation on BCP effects on blood cells. Comparative analysis of BCP and calcium supplemented-BCP (BCP/Ca) effects on blood cells showed that BCP as well as BCP/Ca induced monocyte proliferation, as well as a weak but significant hemolysis. Our data showed for the first time that calcium supplementation of BCP microparticles had anti-inflammatory properties compared to BCP alone that induced an inflammatory response in blood cells. Our results strongly suggest that the anti-inflammatory property of calcium supplemented-BCP results from its down-modulating effect on P2X7R gene expression and its capacity to inhibit ATP/P2X7R interactions, decreasing the NLRP3 inflammasome activation. Considering that monocytes have a vast regenerative potential, and since the excessive inflammation often observed after bone substitutes implantation limits their performance, our results might have great implications in terms of understanding the mechanisms leading to an efficient bone reconstruction. Statement of significance: Although scaffolds and biomaterials unavoidably come into direct contact with blood during bone defect filling, whole blood-biomaterials interactions have been poorly explored. By studying in 3D the interactions between biphasic calcium phosphate (BCP) in microparticulate form and blood, we showed for the first time that calcium supplementation of BCP microparticles (BCP/Ca) has anti-inflammatory properties compared to BCP-induced inflammation in whole blood cells and provided information related to the molecular mechanisms involved. The present study also showed that BCP, as well as BCP/Ca particles stimulate monocyte proliferation. As monocytes represent a powerful target for regenerative therapies and as an excessive inflammation limits the performance of biomaterials in bone tissue engineering, our results might have great implications to improve bone reconstruction.